2006
DOI: 10.1007/s10488-006-0035-5
|View full text |Cite
|
Sign up to set email alerts
|

Residential Mobility and Severe Mental Illness: A Population-based Analysis

Abstract: This research uses population-based administrative data linking health service use to longitudinal postal code information to describe the residential mobility of individuals with a severe mental illness (SMI), schizophrenia. This group is compared to two cohorts, one with no mental illness, and one with a severe physical illness of inflammatory bowel disease. The percentage of individuals with one or more changes in postal code in a 3-year period is examined, along with measures of rural-to-rural regional mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…Because we relied on administrative rather than clinical data to identify the date of incidence cases, this date may not be entirely accurate. However, the diagnostic delay between symptom onset and diagnosis is short and residential mobility rates in Manitoba are low [43]. Further, most migration in North America occurs over short distances to adjacent neighborhoods [44,45;] therefore, it is unlikely that this affected the geographic mapping of our cases.…”
Section: Discussionmentioning
confidence: 99%
“…Because we relied on administrative rather than clinical data to identify the date of incidence cases, this date may not be entirely accurate. However, the diagnostic delay between symptom onset and diagnosis is short and residential mobility rates in Manitoba are low [43]. Further, most migration in North America occurs over short distances to adjacent neighborhoods [44,45;] therefore, it is unlikely that this affected the geographic mapping of our cases.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this view is a recent analysis of the movement patterns of the population of persons residing in the province of Manitoba, Canada; this analysis indicated that people with severe mental illness were twice as likely as others to move to a different postal code within a threeyear period (Lix et al, 2006). The reality of frequent movement raises concern that people with mental illness may experience "displacement" as they relocate to new settings.…”
Section: The Move Toward Scatter-site Independent Housingmentioning
confidence: 99%
“…Although residential mobility itself may not be a direct factor in a woman's health, changing one's address may lead to lack of continuity with a health care provider despite the total number of interactions with the health care system (Lix L et al, 2006). In Manitoba, Lix et al (2006) found that the odds of having at least one address change was associated with older age, gender (higher for males than females), marital status (higher for single and widowed individuals), income (higher for lower income), and the use of hospital and physician services (higher for those who used more services) (Lix L et al, 2006). Frequent changes in residence may also indicate financial instability which may influence the use of screening services (Lix L et al, 2006).…”
Section: Residential Mobilitymentioning
confidence: 99%
“…In Manitoba, Lix et al (2006) found that the odds of having at least one address change was associated with older age, gender (higher for males than females), marital status (higher for single and widowed individuals), income (higher for lower income), and the use of hospital and physician services (higher for those who used more services) (Lix L et al, 2006). Frequent changes in residence may also indicate financial instability which may influence the use of screening services (Lix L et al, 2006).…”
Section: Residential Mobilitymentioning
confidence: 99%
See 1 more Smart Citation